Obtención de matrices carbonadas vegetales activadas mediante la pirólisis de hojas de palma de aceite (2018)
The present work consists of taking advantage of palm leaves of oil from the Camelios de Esperanza crop located in the municipality of Granada in the department of Meta (Colombia) to obtain activated vegetable carbon matrices (MACAVEA). For this, a selection matrix based on the Monte Carlo method was chosen, with which the thermochemical treatment of slow pyrolysis was chosen to be applied to oil palm leaves, after which an experimental design 22 was made, varying the temperature and time of residence to analyze the influence of both variables on the performance of the char, which was found that temperature is the factor that has greater influence on the pyrolytic process, where the highest yield of coal was 35.86 % in operating conditions of 550 ° C and 4 hours. After obtaining it, the coal was chemically activated from 85% H3PO4 at 450 ° C and 15 hours to be subjected to iodine and methylene blue adsorption tests in aqueous solutions, where the presence of micropores and mesopores was estimated.